Artificial caries and dynamic flexural properties of bioactive materials - A/Prof Noor Azlin Yahya; Professor Adrian U Yap; Dr Hui Sing Choo; Dr Hui Yi Choo (Elsevier, 2023)
Aim or Purpose: To investigate the effect of artificial caries on the dynamic flexural properties of bioactive restoratives. Materials and Methods: The materials were: conventional composite (Filtek Z350XT[FZ]) as control, bulk-fill giomer (Beautifil-Bulk Restorative [BB]), bioactive composite (Activa[AB]) and bulk-fill alkasite (Cention N[CN]). Mini beam shaped test specimens (12x2x2mm) were fabricated using customized stainless-steel moulds. For each material, 40 specimens were fabricated. The materials were manipulated according to the manufacturer's instructions where applicable and placed in a single increment into the mould and cured. These were followed by immersion of the specimens in deionized water, remineralization solution, demineralization solution and pH cycle respectively for 14 days under 37°C incubation. Each group of materials (n=10) were then subjected to dynamic mechanical testing in flexure mode at 37°C and frequency of 0.1 to 10Hz. Data normality was checked using Shapiro-Wilk test. Storage modulus, loss modulus, and loss tangent values were obtained and analysed with one-way ANOVA. The difference between artificial caries model for the same material and difference between materials for the same artificial caries model were analysed with Tukey's HSD post-hoc test. Results: Significant differences in dynamic flexural properties were observed between the various bioactive restorative materials and conditioning mediums. BB has the highest storage modulus, AB has the highest loss modulus and tan delta compared to other restorative materials in all conditioning medium. BB was the most stable material with the highest stiffness in all conditioning medium while AB showed the least. Conclusions: The strength of some bioactive materials is compromised by cariogenic challenges. This may impact clinical longevity of restorations, especially in stress bearing areas.